Development and validation of a software to evaluate breathing-induced prostate motion tracked with implanted electromagnetic transponders. (September 2016) - Panaino, C.M.V.; Giandini, T.; Carrara, M.; Frasca, S.; Avuzzi, B.; Morlino, S.; Bosetti, D.; Bedini, N.; Villa, S.; Rancati, T.; Valdagni, R.; Pignoli, E.
Abstract : Introduction: A system (Calypso, Varian Medical Systems) based on the localization of electromagnetic transponders (ELM-TRNs) permanently implanted in the prostate allows real-time tracking during radiotherapy treatments. Purpose: Development and validation of a dedicated software for ELM-TRNs signal analysis to quantify the amplitude of the intra-fraction prostate motion induced by patient's breathing, both in supine and prone position. Materials and methods: For each treatment session, the software automatically identifies the breathing frequency on the power density spectrum of the recorded signal and creates a bandpass filter around this frequency. The obtained filter is then applied to selectively compute the breathing-induced harmonic excursion of the prostate around its nominal position. The software was validated with a moving phantom (QUASAR, Modus Medical Devices), provided with home-made inserts containing three ELM-TRNs. Harmonic motions along the three main directions were tracked at several known frequencies and amplitudes. The calculated frequencies and amplitudes were compared to the expected ones. The software was then applied to signals of patients who underwent radiotherapy treatments in supine or prone position. Results: The software automatically computed the correct frequencies and amplitudes within a 0.6% and a 110 μm uncertainty, respectively, without any significant difference among the three main directions. The software was demonstrated to properly work on signals acquired both with supine and prone patients. Conclusion: A software to quantify prostate motion due to patient's breathing was successfully developed, in-phantom validated and applied to supine and prone patients, highlighting significant motion differences between the two setups. Disclosure: None. Work partially funded by AIRC-(IG-14300).